Analisis Kinerja Simpang Tak Bersinyal Akibat Penerapan Sistem Jalan Satu Arah Menggunakan PKJI 2023 dan Simulasi PTV VISSIM - Sofyan Dayudinata; Anwar Efendy; Adryan Fitrayudha; Isfanari (Jurnal Konstruksi, 2026)
The UMMAT Intersection along the Merdeka–Pagesangan corridor has experienced increasing traffic congestion due to high vehicle volumes and intense surrounding area activities. This study aims to evaluate the performance of the unsignalized intersection under existing conditions and to analyze the impact of implementing a traffic engineering strategy in the form of a one-way road system. The methods used in this study were the Indonesian Highway Capacity Guidelines (PKJI) 2023 and microscopic simulation using PTV VISSIM software. Data were collected through traffic volume surveys, road geometry measurements, and side friction observations. The analysis results indicate that the existing condition operates at a performance level close to saturation. The implementation of the one-way outflow-only scenario tended to reduce intersection performance, whereas the one-way inflow-only scenario demonstrated better performance improvement. Based on the PKJI 2023 analysis, the inflow-only one-way scenario resulted in lower degrees of saturation and delays compared to the existing condition. The PTV VISSIM simulation results also showed a similar pattern, where the inflow-only one-way scenario produced lower intersection delays compared to the outflow-only scenario, although there were differences in the absolute values between the two methods. Overall, the implementation of an inflow-only one-way system on the southern approach (C) proved to be more effective in improving intersection performance through the reduction of traffic conflicts and enhancement of traffic flow orderliness. However, this study has limitations because it focuses only on a single intersection location and does not consider the impact on the overall road network. Therefore, further studies with a broader scope are recommended.